2009
DOI: 10.1111/j.1399-5448.2009.00517.x
|View full text |Cite
|
Sign up to set email alerts
|

Early predictors of myocardial disease in children and adolescents with type 1 diabetes mellitus

Abstract: Asymptomatic diabetics had evidence of subtle right and LV dysfunction with delayed myocardial relaxation which was related to metabolic control. Tissue Doppler (TD) has an additional value in evaluating ventricular filling. NT-pro-BNP is considered a sensitive, specific, and predictive marker for diastolic dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
49
3
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 38 publications
(53 reference statements)
11
49
3
1
Order By: Relevance
“…Such comorbidities may be considered nonexistent in our cohort of diabetic children, who represent a unique model to investigate the early effects of metabolic disturbances induced by type 1 diabetes on myocardial function. Our results are not consistent with the previous studies reported by Salem et al and Khattab where the LV longitudinal function analyzed by TDI was preserved in children and adolescents with type 1 diabetes [10,27] . However, these authors analyzed the velocities of displacement of myocardial walls using pulsed TDI modality, which are more influenced by translational cardiac movements and displacement of adjacent myocardial segments [28] .…”
Section: Left Ventricular Morphology and Functioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Such comorbidities may be considered nonexistent in our cohort of diabetic children, who represent a unique model to investigate the early effects of metabolic disturbances induced by type 1 diabetes on myocardial function. Our results are not consistent with the previous studies reported by Salem et al and Khattab where the LV longitudinal function analyzed by TDI was preserved in children and adolescents with type 1 diabetes [10,27] . However, these authors analyzed the velocities of displacement of myocardial walls using pulsed TDI modality, which are more influenced by translational cardiac movements and displacement of adjacent myocardial segments [28] .…”
Section: Left Ventricular Morphology and Functioncontrasting
confidence: 56%
“…Overall, 30 consecutive children and adolescents with type 1 diabetes (age range [5][6][7][8][9][10][11][12][13][14][15][16][17] years, male: 53%) were recruited at our pediatric endocrinology department and enrolled in this prospective cohort. Among children with diabetes, HBA 1c ranged from 6.8% to 12.7% , 63% of the patients with diabetes patients had HBA 1C > 8 % and mean diabetes duration was 5.1 ± 3.1 years.…”
Section: Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Abnormal ambulatory BP patterns were also associated with higher left ventricular mass in youth with T1DM. 85 Diastolic dysfunction is also common in T1DM, 86 especially in youth with microvascular disease (microalbuminuria or retinopathy), 87 with a prevalence as high as 25% 88 correlated with glucose control. 89 Cardiac mass has also been found to be higher in adolescents with T2DM compared with control subjects 90 with concomitant abnormalities with diastolic filling.…”
mentioning
confidence: 99%
“…Intensive glycemic control improves the cardiac autonomic nerve functions (14). However, measurements of QTc interval are easily obtained without the need for patient compliance, and QTc analysis is a simple, inexpensive, and noninvasive test that could be used to stratify the death risk in diabetic patients (25).…”
Section: Discussionmentioning
confidence: 99%